Informatics applied to health evaluation and promotion: online platform for filling in questionnaires - Camargo, Guilhermy; Noll, Priscilla Rayanne Silva; Bento, Carlos Henrique Pereira; Noll, Matias (Revista Interdisciplinar de Promoção da Saúde, 2018)
Objective: This study was conducted with the objective of developing and evaluating a computerized platform for health promotion for workers of the Instituto Federal Goiano Campus Ceres. Method: The system was developed using markup languages (HTML, CSS) for presentation and styling of the interface and programming languages (PHP, JavaScript) for forms data management, connecting to the database, and dynamic user-system interaction. The graphic framework Bootstrap was also used to increase the visual aspect. The main tools employed were the folowing: Atom (for code editing); FileZilla Client (for FTP files maintenance); and phpMyAdmin (for database management). The system was evaluated by means of a questionnaire created for this purpose, which was completed by 41 workers. Results and final considerations: The results indicate that the platform is useful, innovative, and applicable to various worker populations. Health informatics is a continuously expanding area. Thus, efficient and effective information collection and maintainance systems are essential.